HUBUNGAN PENGETAHUAN IBU DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS JAMBESARI - Nuriyah, Dewi Alif Rochmatun; Ekasari, Tutik; Ermawati, Iit (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Malnutrition is a contributing factor to more than half of the total number of deaths in infants. The provision of exclusive breastfeeding within the first hour after birth and skin-to-skin contact between the mother and the baby are crucial factors in the early breastfeeding process, ensuring the baby's warmth and access to colostrum. The purpose of this study was to determine the cornelation between maternal knowledge and exclusive breastfeeding in the working area of Jambesari Primary Health Care Center, Jambesari Darus Sholah. This research was conducted as a quantitative study, with a descriptive correlational design using a cross-sectional approach. The population comprised 80 respondents selected through random sampling technique. The data analysis was performed using the Chi-Square test. The majority of the respondents had good knowledge, accounting for 63 respondents (78.8%). Furthermore, 64 respondents (80%) practiced exclusive breastfeeding for 6 months. The Chi-Square Tests results showed a value of α < 0.05, which means that there is a significant cornelation between maternal knowledge and exclusive breastfeeding in the working area of Jambesari Primary Health Care Center, Jambesari Darus Sholah in 2023. It is recommended to conduct further training for midwives on the practice of exclusive breastfeeding and effective ways to provide information to mothers. Additionally, using an empathetic approach and effective communication while providing nursing care to mothers, including appropriate information and support regarding the importance of exclusive breastfeeding.